Pendampingan Fotografi dan Desain Grafis di Sekolah Menengah Pertama Katolik (SMPK Kesuma) Mataram - Hasbullah Hasbullah; Anthony Anggrawan; Christofer Satria; I Nyoman Yoga Sumadewa; Baiq Fitria Rahmiati (LPPM Universitas Bumigora, 2022)
Condition of the Catholic Junior High School (SMPK Kesuma) in the COVID-19 pandemic has paralyzed the field trip activities programmed by the school every year. With the soaring Covid-19 cases in Mataram, the school replaced the field trip activities with photography and graphic design training. Photography and graphic design training aims to foster students' talents and interests in dealing with the development of science, technology and art in this current era. The method of implementing this training is by simulation and practice of photography and graphic design. Stages The activity begins with a classical presentation of the material, explaining photography techniques using simple tools such as smartphones. Furthermore, providing assistance in the practice of photography and graphic design. Graphic design assistance is carried out using a simple application available on a smartphone to produce Lombok food promotion posters. The photographic work produced becomes the task of cultural arts and the poster work made by students becomes the assessment of the tourism work program..